RESPON GURU PAI TERHADAP PENDIDIKAN AGAMA BERWAWASAN MULTIKULTURAL (Studi Kasus Respon Guru PAI di SMP Negeri I Kota) - Ahmad Ripai (Holistik, 2011)
Cirebon The research was aimed at describing and analyzing the concept of strategic planning implemented by State Islamic Higher College Cirebon including (1) State Islamic Higher College head›s recognition and understanding of the strategic planning concept, (2) formation of State Islamic Higher College›s strategic planning, (3) implementation of State Islamic Higher College›s strategic planning, and (4) control and evaluation of State Islamic Higher College›s strategic planning. In this qualitative research with phenomenological approach, the researcher became the primary instrument. The data were collected through observation, interview, and documentation, and analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display and data conclusion. Data validity was measured by stretching the time of the research, continuous observation, peer checking, suffcient reference, triangulation, and detailed explanation. The result reveals that (1) the Head of State Islamic Higher College Cirebon recognizes and understands the strategic planning concept through the process of analysis of several educational planning literature, from the expert planners, government, higher education, and internal study in State Islamic Higher College Cirebon. (2) The strategic planning is made by a team formed by Head of State Islamic Higher College Cirebon. Its process begins with strategic direction containing basic outlines of educational development strategy further translated by State Islamic Higher College as executor of education whose formula are in the form of master plan of development. (3) The implementation of the strategic planning in State Islamic Higher College begins with the socialization of the vision, mission, goal, and objective to be reached from the higher level to the lower one, like study program and the units. (4) The control and evaluation done by the Head of State Islamic Higher College in monitoring the implementation of the strategic planning is conducted continously both in a monthly meeting, accidentally meeting and every year to plan the budget of each Faculty, Departement, and non structural unit in State Islamic Higher College